2018
DOI: 10.1007/s11356-018-1266-1
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected potential protective associations between outdoor air pollution and cataracts

Abstract: Air pollution is one of the biggest public health issues, and the eye is continuously exposed to multiple outdoor air pollution. However, to date, no large-scale study has assessed the relationship between air pollutants and cataracts. We investigated associations between outdoor air pollution and cataracts in the Korean population. A population-based cross-sectional study was performed using data from the Korea National Health and Nutrition Examination Survey, including 18,622 adults more than 40 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 29 publications
0
36
1
Order By: Relevance
“…Previous studies examining the association between exposure to air pollution and cataract have shown inconsistent findings and have been limited by their cross-sectional design, smaller sample size, and have only been examined in the Asian populations. 9 , 15 , 16 In a cross-sectional study of 5871 participants, a 1-SD increase in years of biomass fuel use was associated with a 28% increase in nuclear cataract for women in the Indian Eye Study, respectively. 16 In contrast, the KNHANES of 18,622 participants reported that higher ozone concentrations was associated with lower odds of cataract, whereas no significant association was identified between PM 10 and NO 2 with cataract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies examining the association between exposure to air pollution and cataract have shown inconsistent findings and have been limited by their cross-sectional design, smaller sample size, and have only been examined in the Asian populations. 9 , 15 , 16 In a cross-sectional study of 5871 participants, a 1-SD increase in years of biomass fuel use was associated with a 28% increase in nuclear cataract for women in the Indian Eye Study, respectively. 16 In contrast, the KNHANES of 18,622 participants reported that higher ozone concentrations was associated with lower odds of cataract, whereas no significant association was identified between PM 10 and NO 2 with cataract.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In contrast, the KNHANES of 18,622 participants reported that higher ozone concentrations was associated with lower odds of cataract, whereas no significant association was identified between PM 10 and NO 2 with cataract. 9 There has only been one longitudinal study that examined the relationship between ambient air pollution and cataract. 3 In a prospective Korean cohort (NHIS-NSC) of 115,728 participants, higher exposures to PM 10 , NO 2 , and SO 2 were associated with higher risk of cataract, whereas there was no significant association between PM 2.5 and incident cataract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships have been identified between PM 2.5 and visual impairment, 10 glaucoma, 11 , 12 and AMD, 13 but the results for cataract are unclear. 14 , 15 To our knowledge, all of the existing studies have been done in east Asia or the United Kingdom with none being done in the United States or Canada. Some evidence indicates that these findings are biologically plausible.…”
mentioning
confidence: 99%
“…Ultraviolet light exposure is one of the main sources in oxidative stress. The possible mechanism of the protective effect could be that increasing levels of tropospheric O 3 may shield the lens from ultraviolet light exposure (Choi et al, 2018). However, there is another possible reason for cataract formation in people who have household fuel air pollutants exposure, which is high temperature of the working environment.…”
Section: Gaseousmentioning
confidence: 99%